2004
DOI: 10.1051/0004-6361:20040071
|View full text |Cite
|
Sign up to set email alerts
|

AGN and starburst radio activity in the A3558 cluster complex

Abstract: Abstract. We present Very Large Array (VLA) 1.4 GHz (21 cm) observations of the region between the centres of A3558 and A3562, in the major cluster merger complex of the Shapley Concentration. Our final catalogue includes a total of 174 radio sources above the flux density limit of 0.25 mJy b −1 . By cross-correlation with optical and spectroscopic catalogues we found 33 optical counterparts belonging to the Shapley Concentration. We investigated the effects of cluster merger on the radio emission properties o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 50 publications
6
36
0
Order By: Relevance
“…By plotting the adaptively smoothed isodensity contours of all galaxies in this bin, we found that the overdensity coincides with two galaxy clumps close to each other (∼4 Mpc). This fact is consistent with the claim of Owen et al (1999) that cluster merging triggers radio emission (see also Giacintucci et al 2004). Unfortunately, no velocity dispersion estimate is possible because the two clumps are located just outside the region covered by the spectroscopic survey.…”
Section: The Redshift Distributionssupporting
confidence: 93%
“…By plotting the adaptively smoothed isodensity contours of all galaxies in this bin, we found that the overdensity coincides with two galaxy clumps close to each other (∼4 Mpc). This fact is consistent with the claim of Owen et al (1999) that cluster merging triggers radio emission (see also Giacintucci et al 2004). Unfortunately, no velocity dispersion estimate is possible because the two clumps are located just outside the region covered by the spectroscopic survey.…”
Section: The Redshift Distributionssupporting
confidence: 93%
“…But alongside there also are contradictory findings according to which mergers may as well strip away gas from galaxies and result in inhibition of both the processes (e.g. see Giacintucci et al 2004). Thirdly, a configuration containing a NCC cluster with zero mass deposition rate and a central radio source may be obtained through a merger between a NCC cluster and a CC cluster, latter harboring a central AGN, in such a way that it results in disruption of the cool core and leaves behind only traces of the past cooling activity.…”
Section: Cooling and Agn Activitymentioning
confidence: 99%
“…However, Best et al (2005) claim that the phenomena generating the emission lines and the radio emission are statistically independent, even if recent results indicate that radio-loud emission-line AGN favour higher densities than radio-quiet ones (Kauffmann et al 2008) (see also Caputi et al 2009, for a study in the IR). Secondly, only specific environments have been considered, mainly clusters or groups (Miller et al 2002;Hill & Lilly 1991;Giacintucci et al 2004), and therefore we are lacked coverage of a large dynamical range of densities.…”
Section: Introductionmentioning
confidence: 99%